2019
DOI: 10.3390/en12040591
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Effects of Energy and Environmental Efficiency at China’s Provincial Level

Abstract: China’s economic development status continues to grow, but its environmental degradation issue is also becoming a global concern. This study uses dynamic network data envelopment analysis (DN-DEA) to evaluate the energy using efficiency and environmental efficiency in China over the period 2014–2017. The result shows that the former is greater than the latter for all years. This study utilizes a policy-oriented matrix to find the relationship between energy efficiency and Malmquist productivity index (MPI), sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…The abovementioned wastewater discharge (WD), COD, other major pollutants (OMP) are bad outputs. We refer to Hsieh et al and Ma et al [26,27] to adjust bad outputs, as good output variables, and utilize the maximum emission value of each bad output in all DMUs as the base; whereby the adjustment value equals (maximum value of DMUs -original emissions value of each DMU) + 1 to become good outputs. These results illustrate the relationships among rapid economic growth, water resources' use policy, and environmental degradation in China at the provincial level, thus spurring local governments to make a careful assessment of appropriate related policies when actively targeting economic development at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…The abovementioned wastewater discharge (WD), COD, other major pollutants (OMP) are bad outputs. We refer to Hsieh et al and Ma et al [26,27] to adjust bad outputs, as good output variables, and utilize the maximum emission value of each bad output in all DMUs as the base; whereby the adjustment value equals (maximum value of DMUs -original emissions value of each DMU) + 1 to become good outputs. These results illustrate the relationships among rapid economic growth, water resources' use policy, and environmental degradation in China at the provincial level, thus spurring local governments to make a careful assessment of appropriate related policies when actively targeting economic development at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate the GEEE and energy environmental productivity change (EEPC), we took capital stock and labor as non-energy input x , energy consumption as energy input e , actual regional GDP as desirable output g [ 16 , 39 ], and three waste emissions as undesired output b . The selection and processing of input-output indicators are as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Chen and Jia (2017) used SBM by considering undesired output in order to measure environmental efficiency of different regions in China. Ma et al (2019) employed the DN‐DEA method to evaluate and analyze China's energy efficiency and environmental efficiency from 2014 to 2017 and found that annual energy efficiency is higher than environmental efficiency. Xu et al (2021) measured the environmental efficiency of China's heavily polluting industries from both dynamic and static perspectives using SBM and considering undesired outputs and the Malmquist index (MI).…”
Section: Literature Reviewmentioning
confidence: 99%